THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT NUDAS WEDDING DECORATION AT MAJJELLING JALAN GANGGAWA - Kurniawan Kurniawan; Nurfatmawiyanti Nurfatmawiyanti; Auliyah Nurwafiyyah (Jurnal Mahasiswa Manajemen, 2025)
Nudas Wedding Decoration is one of the companies in the service sector. Namely wedding Organiczer, which provides servise to serve wedding events. This study aims to determine the effect of service quality on customer satisfiction at Nudas wedding decoration. This study usus descriptive methods with correlational rsearch types. The population ini this study were all costumers who had used the services of Nudas wedding decoration. The research sampel was selected using a nonprobabiliy sampling approach with accidental sampling technique with the lemeshow formula with sample size of 96 respondents. The data collection technique in this study used a quaestionnaire. The data analysis techniques used are descriptive statistics. Inferential statistics, Inferential statistics, validity test, reliability test, classical assumption test which consists pf normality test, heteroscedasticity test, autocorrelation test and statistical hypothesis testing which consists of determination coefficient test (R2) and t test (parsial test). The results of research on service quality (X) have a positive and significant effect on costumer satisfaction (Y) Nudas Wedding Decoration Jalan Ganggawa Sidenreng Rappang. These results indicate that the better the quality of service provided to customers, the customers satisfation will also increase.